Sustainable Supply Chain Practices and Performance of Manufacturing Firms in Kenya - Mohammed , Z. C.; Lagat , C.; Ngeno , V. (African Journal of Education,Science and Technology (AJEST), 2019)
The main objective of the study was to establish the influence of environmental, social and economic sustainable supply chain practices on the achieveaments of manufacturing firms within Kenya. Survey data collected from 281 Kenyan manufacturing firms were used to test study hypotheses. The researchers adopted explanatory research design and proportionate sampling was used to sample respondents. From the SEM model, results showed that environmentally sustainable supply chain practice (β1 = .303, p<.05), socially sustainable supply chain practice (β2 = .492, p<.05) and economically sustainable supply chain practice (β1 = .626, p<.05), positively influence the outcome of manufacturing firms. Therefore this study concluded that supply chain managers of manufacturing firms should implement social, economic and environmental sustainable supply chain practices in their manufacturing firms to enhance performance. Environmental sustainability practices such as recycling of materials, adoption of cleaner production techniques and adoption of environment management systems must be put in place to enhance the outcome of manufacturing firms. In addition, sustainable social supply chain practices such as improved working conditions, provision of health and safety requirements and promotion of support to the community should be implemented by manufacturing firms to increase their performance. The firm should also put in place measures to increase their utilization of assets and embrace improved manufacturing technologies that improve performance. The study recommended a further study on the same with the inclusion of service sectors and additional dimensions of sustainability such as ethical and supply chain integration dimension apart from economic, social and environmental practices.